Ways Of Depropriating Images - Díaz, Sónia; Martinez, Gabriel (Design/Arts/Culture, 2025)
Looking is a conscious act, a political act, which demands a slow tempo. The gaze is altered by the direct experience of the observer and by the social context in which the image is inscribed, establishing a non-mechanical relationship between art and its context. What defines each epoch is its way of looking and depropriating, of questioning limits and expanding the thresholds that limit us. But what is the way of looking in our times? How can we freely create a new activist sphere with real subversive power?